Identification of a TeO32− reductase/mycothione reductase from Rhodococcus erythropolis PR4. Issue 1 (11th November 2020) - Butz, Zachary J; Hendricks, Alexander; Borgognoni, Kanda; Ackerson, Christopher J
ABSTRACT: A Rhodococcus erythropolis bacterium that tolerates normally lethal concentrations of Fe(II), Cu(II), AsO3 2−, SeO3 2−, TeO3 2−, Cd(II) and Zn(II) was identified from an environmental isolate. In characterizing the molecular basis for metal tolerance, a mycothione reductase (Mtr) with remarkable selectivity for TeO3 2− reduction over SeO3 2− was identified. In equimolar concentrations of TeO3 2− and SeO3 2−, the enzymatic product contains a 7-fold excess of Te. This selectivity is remarkable because the standard reduction potential of SeO3 2− is 0.20 V more favorable for reduction than TeO3 2 . Selectivity of the enzyme for TeO3 2− decreases with increasing assay pH. Homology modeling of the enzyme identifies four aromatic residues near the active site, including two histidine residues, that are not present in a related SeO3 2− preferring reductase. On the basis of more favorable π -interactions for Te than for Se and the pH dependence of the selectivity, the Te-selectivity is attributed in part to these aromatic residues. The resulting Te 0 enzymatic product resembles Te nanowires. Abstract : A novel enzyme selective for tellurium reduction was isolated from an environmental sample and characterized.